A preliminary study on Industry 4.0 as a platform for University-Industry Collaboration - Ungku Shamir, Hamzah; Muhammed Nafis, Osman Zahid (Institution of Engineering and Technology, 2022)
This is an organizational study on a group of companies which are vendors to Original Equipment Manufacturer (OEMs) in the automotive industry in Malaysia. The writer seeks to study on significance of Industry 4.0 in the collaboration between the university and industry. Key personnel from selected subsidiaries of this group of companies were given questionnaires to provide answers on the reasons and advantages in collaborating with universities, models of relationship, the projects developed with the universities and lastly the status and successes working with the universities. The main reason for the industry to work with the university in Industry 4.0 is that the latter has the latest knowledge in this field, they make the best partner and offers advantages such as flexibility and customisation to meet the industry’s requirements. Universities’ most attractive in feature in collaboration is that the knowledge can be shared and they are able to provide assistance in getting grants. The current mode of relationship is universities engaged as consultants and many believed that partnership would be the best form of relationship between the industry and the universities. Automation and Artificial Intelligence are mostly the projects being developed. The current success rate is only slightly more than 50% with the main challenge being the universities’ inability in keeping the same speed with the industry. However, despite the challenges, Industry 4.0 is still deemed as the best platform for university-industry collaboration.